2017
DOI: 10.3892/ijo.2017.3937
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of Frizzled 2 expression and its association with epithelial-to-mesenchymal transition in hepatocellular carcinoma

Abstract: The epithelial-to-mesenchymal transition (EMT) is an initial, critical step in hepatocellular carcinoma (HCC) tumor invasion and metastasis. Frizzled 2 (Fzd2) expression might drive EMT through the non-canonical Wnt pathway, one of the various EMT signaling pathways. The expression of epithelial (E-cadherin) and mesenchymal (vimentin) markers, as well as that of Wnt5b, Stat3, IL-6, Jak2 and Fzd2, were measured in 15 HCC cell lines. The EMT status (vimentin to E-cadherin mRNA expression ratio), Fzd2 mRNA expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Among them, a study has revealed that FZD2 drives EMT and cell metastasis through a previously unrecognized, noncanonical pathway that involves molecules such as the tyrosine kinase (FYN) and STAT3 . Another study confirmed that FZD2 upregulation was significantly correlated with EMT status in HCC …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, a study has revealed that FZD2 drives EMT and cell metastasis through a previously unrecognized, noncanonical pathway that involves molecules such as the tyrosine kinase (FYN) and STAT3 . Another study confirmed that FZD2 upregulation was significantly correlated with EMT status in HCC …”
Section: Introductionmentioning
confidence: 99%
“…9 Another study confirmed that FZD2 upregulation was significantly correlated with EMT status in HCC. 10 Epithelial-mesenchymal transition has been associated with CSC properties and VM in several tumors. [11][12][13] Cancer stem cells are a small subgroup within tumors that are capable of selfrenewal and maintain tumor-initiating capacity through differentiation into the heterogeneous nature of tumor cells that comprise the primary tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have demonstrated the involvement of several Frizzled receptors, including FZD8, FZD2, FZD3, FZD4, FZD5, FZD6, FZD7, and FZD10 in different cancers. Though Frizzled receptors function as key components of the Wnt signaling pathway, the specific link with the ETS‐related transcription factor ERG is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a number of Wnt5a receptors were reported, including Fzd2, Fzd3, Fzd4, Fzd5, Fzd6, Fzd7, Fzd8, RYK, ROR2 and CD146 . Results from several independent studies indicated that Fzd2 expression might drive EMT through the non‐canonical Wnt pathway in different cancer cells . Gujral et al reported that Wnt5a and its ligand Fzd2 are overexpressed in several metastatic cancer cell lines and tumours.…”
Section: Discussionmentioning
confidence: 99%